(untitled) (Journal of Ideas in Health, 2025)
Background: Cardiovascular reactivity to stress was revealed to be a predictor of future cardiovascular risk. A positive family history of hypertension is an important risk factor for the development of hypertension in the children of hypertensive parents. We applied cold pressor test (CPT) to measure heart rate variability (HRV) with the objective to assess the cardiovascular autonomic response to stress. Methods: A case-control study was conducted between from December 2022 to November 2023 at the department of Physiology, Government Medical College, Kota in India. A total of 70 Cases and 70 Controls underwent to CPT technique to evaluate the autonomic function to stress. Descriptive and bivariate analysis including Mann-Whitney U-and ANOVA tests were performed. Results: In this study, the mean ± SD values of HRV in control group before CPT was 79 ± 13, during CPT was 81 ± 11 and after CPT was 77 ± 9. The HR in control group was increased during CPT and the level decreased after CPT. The HRV level in control group was statistically significantly different before CPT, during CPT and after CPT, and p= 0.04. Conclusion: The autonomic measurements were found higher in offspring of hypertensive parents (OHTPs) compared to offspring of normotensive parents (ONHTPs). The offspring of hypertensive parents have higher chances of future development of hypertension than the offspring of normotensive parents.